Legal Dilemma for Land Deed Officials in Transferring Land Title Within Agrarian Reform in Indonesia: A Study in Aceh Province - Rahmah, Siti; Jalil, Husni; Kadir, M.Yakub Aiyub (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The agrarian reform policy in Indonesia is expected to reduce inequality in land ownership and control, provide legal certainty and reduce land disputes by making various changes to legislation and government policies. This article aims to explore the dilemma of transferring land rights in Indonesia in terms of legal certainty and justice for Land Deed Making Officials (Pejabat Pembuat Akta Tanah/PPAT) who have often faced legal proceedings, referring to cases in Aceh Province, Indonesia. This research uses empirical juridical methods with a case study approach, data collection techniques, interviews, observation and document study. The results of the research show that Land Deed Making Officials have a high legal risk in transferring land rights in Indonesia, especially if there are deviations, errors or mistakes in the procedures for making deeds, so that Land Deed Making Officials are held administratively, civilly and criminally responsible. This problem occurs because of differences in interpretation regarding PPAT's obligation to carry out field verification, lack of legal protection, and lack of village-based land data. This study offers new insights into strengthening customary land database institutions at the village level supported by the National Land Agency. So, this offer helps unravel the complexity of the land transfer process and offers a potential solution for better justice for Land Deed Making Officials under the Jokowi government's agrarian reform, and guarantees justice and certainty for land owners, as a way to achieve the welfare of the people in Indonesia.